Pelatihan dan Pendampingan Pembuatan Kemasan Onde–onde Ketawa untuk Meningkatkan Daya Jual Produk pada UMKM Mugi Berkah - Syakhroni, Akhmad; Khoiriyah, Nuzulia; Marlyana, Novi; M Maknun; Mas'ud, Ahmad Afifudin (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Competition in the world of Micro, Small, and Medium Enterprises (MSMEs) is currently very tight, requiring business players to constantly innovate to survive, not only in terms of product quality but also in packaging. Product packaging in MSME competition is a significant challenge that must be faced by MSMEs in marketing their products. UMKM Mugi Berkah is a home industry that produces snacks called "Onde-onde Ketawa." The products from this home industry are marketed directly around the Penggaron-Semarang area and also through social media. The current packaging uses plain plastic, which cannot be resealed once opened. The existing packaging and label are perceived as less attractive in some parts, especially the back of the packaging, which still looks plain or empty, without product information such as product net weight, expiration date, and other important information about the product. MSMEs need to be equipped not only with an understanding of the importance of having competitive packaging in the market but also with skills in making packaging, so they can have their own more attractive packaging to market their products.Community service activities are carried out through: Education on the concept of packaging, Training in packaging design, Assistance in making packaging. These community service activities not only provide MSME owners with an understanding of the importance of competitive packaging but also produce three types of packaging in blue, purple, and yellow. Consumer survey results on the new packaging model indicate that the packaging is attractive, informative, safe to carry while traveling, and more durable.